Effect of laser photocoagulation and bevacizumab intravitreal in proliferative diabetic retinopathy: review on biomarkers of oxidative stress (Medical Journal of Indonesia, 2014)
Background: This study was aimed to compare the effect of laser photocoagulation (LF), intravitreal bevacizumab (IVB) and combined treatments on biomarkers of oxidative stress such as aldehhyde dehidrogenase (ALDH), malondialdehyde (MDA) level, superoxide dismutase (SOD) activities, and vitreal vascular endothelial growth factor (VEGF) on proliferative diabetic retinopathy (DR) patients. Methods: In this single blind randomized clinical trial, 72 eyes from 69 cases of proliferative DR in Cipto Mangunkusumo Hospital between February 2011 - June 2013 were randomized into 4 groups : 1) control (n = 18); 2) LF pre-vitrectomy (n = 18); 3) IVB pre-vitrectomy (n = 18); and 4) combined IVB and LF pre-vitrectomy (n = 18). One-way ANOVA was used to compare oxidative stress parameters in the four groups. Results: There were no statistically significant differences in the average plasma ALDH activity (0.034 ± 0.02; 0.027 ± 0.02; 0.025 ± 0.02; 0.031 ± 0.11 IU/mg protein; p = 0.66), vitreal MDA level (1.661 ± 1.21; 1.557 ± 1.32; 1.717 ± 1.54; 1.501 ± 1.09 nmol/mL; p = 0.96) and SOD activity) (0.403 ± 0.50; 0.210 ± 0.18; 0.399 ± 0.49; 0.273 ± 0.32 U/mL; p = 0.38) among these four groups, respectively. However, the VEGF vitreal level (pg/mL) showed a statistically significant difference (0.356 ± 0.60; 0.393 ± 0.45; 0.150 ± 0.24; 0.069 ± 0.13; p = 0.05). The VEGF level in combination group was five times lower than the control group (p = 0.05). Conclusion: Combined treatments of DR by IVB and LF were correlated with lower vitreal MDA and plasma VEGF level, but did not have any effect on plasma ALDH and vitreal SOD in proliferative DR. Combined treatments with IVB and LF are recommended for the management of proliferative DR patients.